2021
DOI: 10.3390/en14196071
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Energy Conversion Systems with Sliding Mode Control

Abstract: A new sliding-mode-control-based power conversion scheme is proposed for photovoltaic energy conversion systems. The perturbation and observation (P&O) maximum power-point tracking (MPPT) approach is adopted for optimizing the power generation capabilities from solar panels. Due to the inherent nonlinear dynamics of power converters, we need to adopt a nonlinear control approach to optimize the energy conversion efficiency and tolerate the fluctuations and changes of load and sunlight irradiance. In this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…(3) Energy storage criterion: This criterion is defined by function (10) and indicates how successful the control system has been in energy storage. Obviously, the higher the value of the function (29), the more successful the system is in storing energy.…”
Section: Simulation and Testing Of The Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Energy storage criterion: This criterion is defined by function (10) and indicates how successful the control system has been in energy storage. Obviously, the higher the value of the function (29), the more successful the system is in storing energy.…”
Section: Simulation and Testing Of The Proposed Methodsmentioning
confidence: 99%
“…In [27], a battery-supercapacitor system was set up using PI-PSO hybrid control. However, the most powerful and widely used control theory for hybrid systems, including batteries, is sliding mode control [28,29]. Studies have shown that the sliding mode method has been very successful in controlling these systems and, therefore, this method was used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The SMC responds rapidly and is not affected by system parameter perturbations, external disturbances, etc. [25][26][27]. Given that the variable structure characteristics of sliding-mode control are similar to the switching characteristics of ES converters, we apply it to the control of ESs.…”
Section: Introductionmentioning
confidence: 99%
“…Since a PV setup has a low efficiency, the MPPT is an essential step because it helps the system to achieve the best overall performance [28]. This can be generated through a designed control technique that can be embedded in a DC-DC converter [29].…”
Section: Introductionmentioning
confidence: 99%
“…The control signal of a SMC is composed of an equivalent u eq and a switching term u sw , which are established in Equation (9). The first mentioned is achieved based on the condition Ṡ = 0 [28]; the switching, which guarantees robustness, is expressed in Equation (10). u = u eq + u sw (9)…”
mentioning
confidence: 99%